Tolerance of biofilm of a carbapenem-resistant Klebsiella pneumoniae involved in a duodenoscopy-associated outbreak to the disinfectant used in reprocessing - Brunke, Melanie Sarah; Konrat, Katharina; Schaudinn, Christoph; Piening, Brar; Pfeifer, Yvonne; Becker, Laura; Schwebke, Ingeborg; Arvand, Mardjan (Antimicrobial resistance and infection control, 2022)
One possible transmission route for nosocomial pathogens is contaminated medical devices. Formation of biofilms can exacerbate the problem. We report on a carbapenemase-producing Klebsiella pneumoniae that had caused an outbreak linked to contaminated duodenoscopes. To determine whether increased tolerance to disinfectants may have contributed to the outbreak, we investigated the susceptibility of the outbreak strain to disinfectants commonly used for duodenoscope reprocessing. Disinfection efficacy was tested on planktonic bacteria and on biofilm.